Asian Settler Colonialism From Local Governance to the Habits of Everyday Life in Hawaii - Fujikane, Candace; Okamura, Jonathan Y. (University of Hawaii Press, 2008)
Asian Settler Colonialism is a groundbreaking collection that examines the roles of Asians as settlers in Hawai‘i. Contributors from various fields and disciplines investigate aspects of Asian settler colonialism to illustrate its diverse operations and impact on Native Hawaiians. Essays range from analyses of Japanese, Korean, and Filipino settlement to accounts of Asian settler practices in the legislature, the prison industrial complex, and the U.S. military to critiques of Asian settlers’ claims to Hawai‘i in literature and the visual arts